Surface Roughness and Bacterial Adherence to Resin Composites and Ceramics - Kantorski, Karla Zanini; Scotti, Roberto; Valandro, Luiz Felipe; Bottino, Marco Antonio [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Jorge, Antonio Olavo [UNESP] (Quintessence Publishing Co Inc, 2009)
Purpose: The aim of this study was to evaluate the surface roughness and the in vitro adherence of Streptococcus mutans to indirect aesthetic restorative materials that are uncoated with saliva.Materials and Methods: Four groups of restorative materials were evaluated according to material type: (1) microparticulate feldspathic ceramic; (2) leucite-reinforced feldspathic ceramic; (3) microhybrid resin composite and (4) microfilled resin composite. Twenty standardised samples of each material were produced. Roughness analysis (Ra, n = 10) was performed using a roughness analyser. Adhesion tests (n = 10) were carried out in 24-well plates; colony-forming units (CFU/mL) were evaluated. The mean values of roughness (mu m) and adherence (CFU/mL) for each group were subjected to an analysis of variance and a Tukey test.Results: The leucite-reinforced feldspathic ceramic was rougher and presented higher bacterial adherence than the microparticulate feldspathic ceramic. The resin composites were similar with regard to surface roughness and bacterial adherence.Conclusions: The microhybrid and microfilled resin composites were similar and the leucite-reinforced feldspathic ceramic was rougher and presented higher bacterial adherence than the microparticulate feldspathic ceramic.
Keywords: ceramic; resin composite; Streptococcus mutans; surface roughness